Analyzing the Implementation of Food Security Policies in Indonesia through the MSN Approach (Mentality, System, and Networking) - M. Syukur; Sussanti Sussanti; Srifridayanti Srifridayanti (Department of Public Administration, 2025)
This study aims to describe, analyze, and interpret the implementation of food security policies and strategies in Indonesia using the Mentality, System, and Networking (MSN) approach. The research employs a descriptive method, which is used to understand or depict the reality of the events under investigation. The focus of this study is directed toward three main approaches: the mentality approach, system approach, and networking approach. The researchers chose these three approaches because a public policy will become actual and directed in its implementation if it uses or considers the MSN-Approach Model The conclusions drawn from this study encompass three aspects: Mentality Approach: The attitudes, behaviors, and responsibilities of officials have demonstrated a caring attitude. The state has consistently committed to placing the food economy as something very important and strategic. The government's concern is also seen from Indonesia's participation in global food security development initiatives. System Approach: There are clear and explicit regulations regarding the government's obligations to realize food security. Law No. 18 of 2012 serves as evidence of the government's responsibility and seriousness in achieving food security. Networking Approach: This approach has been well implemented, as evidenced by the strengthening of food distribution infrastructure across Indonesia. Given the complexity of geographical challenges and uneven food distribution, the government has established collaborations and synergies with regional governments to build new markets and expand logistics networks connecting food production centers with consumer areas.